Ways to reduce radioactivity accumulation in the kidney during targeted therapy using small molecules, peptides and antibody fragments - K. O. Avrov; S. V. Shatik; M. P. Samoilovich (Сибирский онкологический журнал)
Administration of pharmaceuticals containing radioactive isotopes and capable of specific binding to certain proteins is one of the approaches used in the treatment or diagnosis of malignant tumors. High renal accumulation of radioactive compounds after administration of radioconjugates with molecular mass less than 70 KDa is of the challenges that need to be solved. The purpose of the study was to identify the most effective approaches to reduce the accumulation of radioactivity in the kidneys after administration of radioconjugates used for diagnostic imaging and targeted therapy for cancer. Material and Methods. We conducted a literature search on the topic of the review in the electronic databases PubMed, Scopus and Web of Science from 1987 to 2023, 82 articles were used for writing the review. Results. The review presents a description of approaches used to improve the biodistribution of radioconjugates, mainly in preclinical studies. The advantages and disadvantages of such techniques have been described. Conclusion. Reducing renal radioactivity using radioconjugates of molecules with molecular masses less than 70 KDa is a challenging but achievable task. It is concluded that the use of cleavable linkers in such radioconjugates is highly promising, since this approach does not change the pharmacokinetics of such drugs. It is noted that the advantage of introducing concomitant substances compared to changing the structure of radioconjugates is a lesser dependence on the characteristics of a particular radiopharmaceutical. This approach also does not require prior work to modify the radioconjugate, but has limited efficiency.